HUBUNGAN KUALITAS TIDUR DENGAN RISIKO OBESITAS PADA REMAJA DI SMPN 16 TANGERANG SELATAN - Rizcha Aristiara (2022)
Obesity occurs as a result of an imbalance between energy intake or intake with energy used. Sleep problems in adolescents today can interfere with the body's development process which can have an impact on the risk of obesity which in the future can cause various diseases. This study aims to determine the relationship between sleep quality and the risk of obesity in adolescents at SMPN 16 South Tangerang. This study used a cross-sectional research design with a sample of 152 respondents using purposive sampling method. The results of the study based on the analysis using the Chi-square test showed that there was a relationship between sleep quality and the risk of obesity (p value = 0.023). The suggestion from this researcher is that adolescents can pay attention to the balance between sleep and activities carried out or eating patterns in order to avoid the risk of obesity.